Sarcopenia en pacientes adultos mayores, métodos de diagnóstico y tratamiento nutricional - Loayza Montalvan, Jinsop David (Machala : Universidad Técnica de Machala, 2024)
Introduction: Sarcopenia is defined as the progressive and generalized loss of muscle mass and strength to the point of making proper musculoskeletal function impossible in older adults. Aging encompasses the pathophysiological mechanisms that cause sarcopenia, such as the loss of alpha motor neurons, hormonal changes, and increased oxidative stress, among the main ones. Objective: Define the methods of diagnosis and nutritional treatment of sarcopenia in older adult patients through the review of high-impact scientific articles to be applied in clinical practice. Methodology: Descriptive bibliographic review, where the Regional Portal of the Virtual Health Library (VHL) was used to search for key words related to the research, validated information was collected in scientific databases such as Ebsco, Scopus, PubMed, Scielo, Google scholar, National Institute of Statistics and Census, related to sarcopenia in older adults, published from 2019 to July 2024. For the selection of articles, those quartiles 1 and 2 were considered, mostly, English and Spanish language, free full text, those published older than 5 years were excluded. Results: There are a variety of tests and techniques that can be applied for diagnosis, however, in clinical practice bioimpedance is used to confirm the diagnosis. Conclusion: The treatment of sarcopenia is a comprehensive management, it must incorporate the consumption of proteins of high biological value together with resistance exercise, they exert a synergistic effect on muscle tissue.
Introducción: La sarcopenia se define como la pérdida progresiva y generalizada de la masa y fuerza muscular hasta el punto de imposibilitar la correcta función musculo esquelética en los adultos mayores. El envejecimiento engloba los mecanismos fisiopatológicos causantes de la sarcopenia, como la pérdida de motoneuronas alfa, cambios hormonales, aumento del estrés oxidativo, entre los principales. Objetivo: Definir los métodos de diagnóstico y tratamiento nutricional de sarcopenia en pacientes adultos mayores mediante la revisión de artículos científicos de alto impacto para ser aplicados en la práctica clínica. Metodología: Revisión bibliográfica de tipo descriptiva, donde se empleó el Portal Regional de la Biblioteca Virtual en Salud (BVS) para la búsqueda de palabras claves relacionadas a la investigación, se recopiló información validada en base de datos científicas como Ebsco, Scopus, PubMed, Scielo, Google académico, Instituto Nacional de Estadísticas y Censo, relacionadas a sarcopenia en adultos mayores, publicada desde el año 2019 hasta julio del 2024. Para la selección de artículos se consideraron aquellos cuartiles 1 y 2 en su mayoría, idioma inglés y español, texto completo gratis, se excluyeron aquellos publicados mayor a 5 años. Resultados: Existen variedad de test y técnicas que pueden aplicarse para el diagnóstico, sin embargo, en la práctica clínica se utiliza la bioimpedancia para confirmar el diagnóstico.
Keywords: SARCOPENIA; ADULTO MAYOR; SUPLEMENTO NUTRICIONAL